New technique for endoscopically-assisted particulate graft reconstruction of the mandible. Issue 5 (June 2018) - Ferretti, C.; Reyneke, J.; Heliotis, M.; Ripamonti, U.
Abstract: The reconstruction of mandibular defects using particulate grafts is a proven technique that restores the osseous anatomy effectively. Secondary osseous reconstruction can be accomplished with endoscopic assistance and reduced-access incisions if an intermediate spacer is placed during resection. Two patients required reconstruction after resection of mandibular ameloblastomas. We used a modified protocol that involved the implantation of a graft of particulate corticocancellous bone after removal of the spacer, and prepared the recipient site under endoscopic guidance with small extraoral incisions. The grafts healed uneventfully and matured into ossicles suitable for the placement of osseointegrated implants.